2014
DOI: 10.1111/aos.12310
|View full text |Cite
|
Sign up to set email alerts
|

Ocular dimensions in relation to auxological data in a sample of Swedish children aged 4–15 years

Abstract: ABSTRACT.Purpose: The purpose was to characterize normal growth patterns of ocular and optical components and to relate them to auxological data in a sample of Swedish children aged 4-15 years. Methods: A prospective cross-sectional study was carried out in 143 Swedish children with a mean age of 9.8 years. Variables including gestational age (GA), weight, length and head circumference (HCF) at birth and at the time of assessment were registered. Visual acuity (VA), cycloplegic refraction and biometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…Indeed, Grey et al 21 found that narrowing the palpebral aperture leads to increased cylindrical error, while Read et al 22 reported that corneal cylinder axis correlates with the eyelid angle. Nevertheless, Raffa et al 23 did not find an association of palpebral fissure length with gestational age or birthweight.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, Grey et al 21 found that narrowing the palpebral aperture leads to increased cylindrical error, while Read et al 22 reported that corneal cylinder axis correlates with the eyelid angle. Nevertheless, Raffa et al 23 did not find an association of palpebral fissure length with gestational age or birthweight.…”
Section: Discussionmentioning
confidence: 92%
“…Normal growth patterns of ocular and optical components and their relation to auxological data in a sample of Swedish children aged 4–15 years have previously been characterized (Raffa et al. ). The aim of this study was to evaluate how moderate‐to‐late prematurity impacts ocular morbidity at the age of 5–6 years and to relate ophthalmological variables to auxological data at birth and at assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growth of this population and the acknowledgement of increased risk in the literature, only limited information is available on the associated ophthalmological complications, the impact of these problems and recommendations for follow-up programmes. Normal growth patterns of ocular and optical components and their relation to auxological data in a sample of Swedish children aged 4-15 years have previously been characterized (Raffa et al 2014). The aim of this study was to evaluate how moderate-to-late prematurity impacts ocular morbidity at the age of 5-6 years and to relate ophthalmological variables to auxological data at birth and at assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from our study, they analysed children aged 6 years, in whom myopia can still develop, and excluded children who had been born before 36 weeks of gestational age. Similarly, a recent study also has reported that refraction is unrelated to birth size or gestational age in Swedish children aged 4–15 years [ 16 ], but this study comprised 143 children and did not include children born at <35 weeks' gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been carried out to find out the relations of refractive error and ocular biometric measures with birth parameters in preterm or low birth weight child at birth and in the long term [ 6 , 9 13 ]. A few studies investigated the association of birth parameters and refraction or biometric parameters in the general population of children [ 14 16 ]. In this cohort study, we aimed to investigate the association of birth parameters (BW, GA, and appropriateness for GA) with refractive status in different age groups of Caucasian children.…”
Section: Introductionmentioning
confidence: 99%